Indoor air pollution: an Italian Knowledge, Attitude and Practice (KAP) study among the general population - Venuto, Roberto; Pappalardo, Roberta; Genovese, Cristina; Trimarchi, Giuseppe; Squeri, Raffaele; La Spada, Giuseppe; La Fauci, Vincenza (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. Indoor air pollution negatively affects population health and the national health services in terms of socio-economic costs. The presence of indoor pollutants depends a lot on lifestyles. Study design. The aim of this work is to evaluate knowledge, daily habits and the preventive behaviors in order to contrast the effects on health caused by indoor pollutants. Methods. The study was conducted through the administration of questionnaires to the population resident in the metropolitan city of Messina (Italy), asking about sociodemographic characteristics, knowledge, daily habits and preventive behaviors. Results. The questionnaire was filled by 894 subjects (46.8% M; 53.2% F). Regarding knowledge, 66.8% had heard of indoor air pollution and 94.9% knew what the most common indoor pollutants are; regarding daily habits they often aired out the house (91.9% in the morning and 71.4% after cleaning), 24.8% were smokers and 36.7 of them smoked indoors; regarding preventive behaviors, 41.6% chose the cleaning products based on habit and only 32.9% bought plants able to purify environments. Conclusions. Although the analyzed population had adequate knowledge of indoor air pollution, this did not strongly impact on the adoption of healthy lifestyles. Therefore, it becomes necessary to intervene on a social level with environmental education activities, starting from school age.